Long-term whole-body vibration induces degeneration of intervertebral disc and facet joint in a bipedal mouse model - Jin, Lin-Yu; Yin, Hong-Lin; Xu, Yi-Qiong; Xu, Shuai; Song, Xiao-Xing; Luo, Yan; Li, Xin-Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Background. Whole body vibration (WBV) has been used to treat various musculoskeletal diseases in recent years. However, there is limited knowledge about its effects on upright posture mouse’s lumbar segments. This study was performed to investigate the effects of axial WBV on intervertebral disc (IVD) and facet joint (FJ) in a novel bipedal mouse model. Methods. Six-week old male mice were divided into control, bipedal and bipedal + vibration groups. Taking advantage of the hydrophobia of mouse, mice in the bipedal and bipedal + vibration groups were placed in a limited water-container and were thus built standing posture for a long time. The standing posture was conducted twice a day for a total of six hours per day, seven days per week. WBV was conducted during the first stage of bipedal building for 30 minutes per day (45 Hz with peak acceleration at 0.3g). The mice of control group were placed in a water-free container. At the end of 10 weeks, IVD and FJ were examined by micro-computed tomography (micro-CT), histologic staining, and immunohistochemistry (IHC), and gene expression was quantified using real-time polymerase chain reaction. Further, a finite element (FE) model was built based on the micro-CT, and dynamic WBV was loaded on the spine model Results. Following 10 weeks model building, IVD showed histological markers of degeneration, such as disorders of annulus fibrosus and increased cell death. Catabolism genes expression, such as Mmp13, and Adamts 4/5, were enhanced in the bipedal groups, and WBV promoted these catabolism genes expression. Examination of the facet joint after 10 weeks of bipedal with/without WBV loading revealed rough surface and hypertrophic changes at the FJ cartilage resembling osteoarthritis. Moreover, IHC results demonstrated that the protein level of hypertrophic markers (Mmp13 and Collagen X) were increased by long time standing posture, and WBV also accelerated the degenerative changes of FJ induced by bipedal postures. No changes in anabolism of IVD and FJ were observed in the present study. Furthermore, FE analysis revealed that larger frequency of WBV loading condition could induce higher Von Mises stress on IVD, contact force and displacement on FJ.